Polymer Synthesis: Theory and Practice - Braun, Dietrich; Cherdron, Harald; Rehahn, Matthias; Ritter, Helmut; Voit, Brigitte (Springer, 2013)
The focus of the previous edition was on a broader description of the general methods and techniques for the synthesis, modifications and characterization of macromolecules. This was supplemented by selected and detailed experiments and by sufficient theoretical treatment so that no additional textbook be needed in order to understand the experiments. In addition to the preparative aspects, we had also tried to give the reader an impression of the relation of chemical structure and morphology of polymers to their properties. This concept is also maintained in this edition. In recent years, the so-called functional polymers (which have special electrical, electronic, optical and biological properties), have attracted a lot of interest. We, therefore, felt, that a textbook should exist that would contain recipes which describe the synthesis of these materials. For this reason, we added a new chapter “Functional Polymers”. Together with new experiments in Chaps. 3, 4 and 5, the book now contains more than 120 recipes that describe a wide range of macromolecules.
Fundamentals, Methods, Experiments